2017
DOI: 10.1200/jco.2017.35.15_suppl.e14532
|View full text |Cite
|
Sign up to set email alerts
|

High baseline lymphocyte count is a predictive biomarker of prolonged time to progression in patients with advanced solid tumors receiving checkpoint inhibitors.

Abstract: e14532 Background: Biomarkers predicting response to checkpoint inhibitor are needed to better select patients most likely to benefit from treatment. We observed that baseline absolute lymphocyte count (ALC) can predict durable responses to anti-PD-1 antibodies in various malignancies. Methods: This is a retrospective analysis of patients with advanced solid tumors treated with anti-PD-1 antibodies. Pembrolizumab was given at 2 mg/kg every 3 weeks, Nivolumab at 3 mg/kg every 2 weeks. Peripheral ALC and absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Past reports have suggested that pretreatment lymphopenia in patients with advanced cancers is a prognostic factor for survival, which supports the conclusion that tumor-induced lymphopenia, preexisting immunosuppressive conditions, or combinations of both factors lead to poor clinical outcome (16). Recent reports regarding poor responses to immune checkpoint inhibitors in patients with lymphopenia support the conclusion that both factors may be associated with treatment results (17,18). Therefore, in EBC patients for whom complete tumor resection is expected, it may be appropriate to evaluate the clinical impact of innate lymphopenia and the ability to overcome this condition.…”
Section: Discussionmentioning
confidence: 73%
“…Past reports have suggested that pretreatment lymphopenia in patients with advanced cancers is a prognostic factor for survival, which supports the conclusion that tumor-induced lymphopenia, preexisting immunosuppressive conditions, or combinations of both factors lead to poor clinical outcome (16). Recent reports regarding poor responses to immune checkpoint inhibitors in patients with lymphopenia support the conclusion that both factors may be associated with treatment results (17,18). Therefore, in EBC patients for whom complete tumor resection is expected, it may be appropriate to evaluate the clinical impact of innate lymphopenia and the ability to overcome this condition.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies have previously assessed the predictive value of various peripheral lymphocyte measures for ICI therapy response, including absolute or relative lymphocyte count at the beginning of treatment, on-treatment, or dynamic changes during treatment. High baseline ALC and increase in ALC during the treatment were associated with better response to anti-PD-1/PD-L1 therapy (4,6,7). Similarly, low NLR and decrease in NLR with anti-PD-1 blockade were associated with improved outcomes in various solid tumors (5,8,9).…”
Section: Introductionmentioning
confidence: 99%